Association between previous health condition and outcome after cardiac arrest. (October 2021) - Dumas, Florence; Paoli, Audrey; Paul, Marine; Savary, Guillaume; Jaubert, Paul; Chocron, Richard; Varenne, Olivier; Mira, Jean-Paul; Charpentier, Julien; Bougouin, Wulfran; Cariou, Alain
Abstract: Introduction: Overall survival of patients with out-of-hospital cardiac arrest (OHCA) remains low, even in those with return of spontaneous circulation (ROSC). In addition to usual prognostic characteristics, patients' medical history may also influence their outcome. This study aimed to investigate the role of pre-arrest comorbidities on hospital survival, neurological outcome and mode of death in OHCA patients with successful ROSC. Methods: From Jan 2012 to Sep 2017, all consecutive non-traumatic OHCA adults, admitted with a stable ROSC were included. Utstein characteristics, circumstances of arrest and interventions were prospectively recorded. Prior comorbidities were measured using the Charlson Comorbidity Index (CCI), and the population was divided into 3 groups (CCI 0, CCI 1–3 and CCI ≥ 4). The association of CCI with early and long-term mortality was assessed using logistic regression and association with withdrawal-of-life sustaining treatments (WLST) or another cause of death using multinomial regression. Results: During the study period, 777 patients were analyzed and 483 (62%) died before hospital discharge, with death rate of 49%, 60% and 70% in CCI 0, CCI 1–3 and CCI ≥ 4 respectively. After adjustment, an increase CCI was significantly associated with in-hospital mortality (OR = 2.47 [1.35–4.52], p = 0.001 for CCI 1–3; OR = 2.82 [1.49–5.33], p = 0.003 for CCI ≥ 4; ref = CCI 0). Other independent predictors were non-shockable rhythm (OR = 3.23 [2.08–5]), lack of bystander CPR (OR = 1.96 [1.22–3.13]), epinephrine dose ≥ 2 mg (OR = 5.56 [3.70–8.33]), CA to CPR ≥ 5 min (OR = 1.96 [1.28–3.03]) and CPR to ROSC ≥ 20 min (OR = 2.13 [1.39–3.23]). Using multinomial regression, an increase in CCI was associated with all modes of in-hospital death, particularly with WLST-related death (RRadj = 2.48 [1.26–4.90], p = 0.01 for CCI = 1–3 and 3.75 [1.85−8.7.58], p < 0.001 for CCI ≥ 4, reference CCI = 0). Conclusion: Alteration of chronic health status, as assessed by an elevated CCI, was associated with a higher mortality and a worse neurological outcome in OHCA patients. Presence and burden of comorbidities should be considered in the evaluation of the prognosis in patients admitted in hospital after cardiac arrest.